Ecological-and-hygienic estimation of cement compositions filled with recycled polymeric waste - Malyshevska, O. S.; Harkavyi, S.I. (Environment & Health, 2019)
Objective: We conducted ecological-and-hygienic assessment of the building materials made of cement compositions filled with recycled polymer waste. Materials and methods: We used building materials made of cement-sand compositions filled with mechanically recycled polymer waste. The data of the instrumental research were obtained by the specialists and with the equipment of the Ivano-Frankivsk Oblast Laboratory Centre, MPHU for the research work N 0117U004237 under field conditions at the certified laboratory centres of Ivano-Frankivsk National Medical University. Those data determined the impact of various aggressive media on the chemical destruction of the cement compositions filled with polymers. The investigations were carried out with the application of PET waste, PCH, and PE + PP mixtures; slag Portland cement; washed sand; device for mechanical activation of polymer waste; homo-mixer; laboratory balance; chemical reagents, and equipment for titration. The calculations were carried out according to SanNR 2.03.11-85 “Protection of building structures from corrosion”, SSU 4079-2001 “Determination of total chloride content”. The preparation of the cement-sand mixture and the study of physical-and-mechanical properties of the samples were made according to the standards EN 12390-5 and EN 206-1. Results and discussion: The results of the research showed that the smallest amount of the destruction products was extracted from the samples filled with PET (from 2% to 8% of the total weight of the filler) when there was a sharp decrease in the mass loss in samples due to the washing of CaO under conditions of carbon dioxide and extensible corrosion and as well as in rain and distilled water. Acceleration of the destruction of studied sample was noted in the magnesian medium; with PVC from 2% to 6%, there is a sharp decrease in the mass loss of the samples under conditions of all simulated corrosive media, as well as in rain and distilled water; with PE + PP mixture, from 0.25% to 1.25%, under conditions of all simulated aggressive media and in rain and distilled water. In our opinion, an increase in the stability of samples of cement compositions, filled with recycled polymers in aggressive media, is due to the formation of more dense structure with a large amount of low basic calcium hydrosilicates and solid solutions of hydroalumosilicate composition. Conclusions and prospects: Hygienic investigations have shown that the product of destruction of the samples of cement-sand compositions, filled with polymers, is a mixture of inorganic amorphous sediment, its main mass consists of CaO, Ca (OH)2, Ca (НСО3)2 from 97.4 % to 98.2 % of the total mass sediment, Mg (OH)2, Al2 (OH)3. Formed products of destruction are non-toxic insoluble or slightly soluble simple inorganic compounds that do not affect adversely the environment and human being. A study of the impact of the destruction products’ formation in the aggressive media of the surfactants, applied on the surface of polymer fillers to improve their adhesion to the components of the cement matrix, will be the main direction of the subsequent research.